Taenia asiatica: Mitochondrial signatures based analysis of an emerging public health threat in India - Aman D. Moudgil; Anil K. Nehra; Pallavi Moudgil (New Microbes and New Infections)
Background: Taenia asiatica is a zoonotic tapeworm, commonly known as Asian Taenia. It is an emerging sister species of T. saginata with pigs as intermediate hosts. The present study aimed at genetic characterization and population structure analysis of T. asiatica metacestodes in slaughtered pigs in Haryana, north India. Methods: In total, the vital organs of 253 slaughtered pigs were screened for the presence of T. asiatica metacestodes. The molecular identification and phylogenetics were performed targeting the mitochondrial NADH dehydrogenase subunit 1 (nad1) and cytochrome C oxidase subunit 1 (cox1) genes. The median-joining haplotype network and population structure analyses were performed with the sequences generated herein and GenBank-archived T. asiatica sequences for both mitochondrial signatures. Results: Out of 253 pigs screened, the liver of only one animal showed the presence of T. asiatica metacestodes. The sequences generated herein exhibited 99.60 % and 98.85 % similarity to the GenBank-archived sequences of T. asiatica corresponding to the nad1 and cox1 genes, respectively. Overall, 2 and 6 haplotypes for the overall data set with low nucleotide (0.00399 ± 0.00237 and 0.00095 ± 0.00042) and low haplotype (0.400 ± 0.237 and 0.131 ± 0.054) diversities were recorded for the nad1 and cox1 genes, respectively. The negative values recorded for the neutrality indices exhibited deviations from neutrality and hence, propounded recent population expansion or purifying selection or selective sweep. Conclusions: The findings of the present study are of significant medical importance considering an emerging global public health threat of the neglected tapeworm T. asiatica.